Parents’ Preparedness in Facilitating Learning and Academic Performance in Grade 9 Science - Lira B. Eduardo; Joji D. Linaugo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
New reality of the education process demands for collaboration between mentors and parents or guardians in guiding the learners to master lessons, obtain knowledge, and master competencies, especially in Science. This study utilized descriptive correlational research design to analyze the preparedness of parents as facilitator of learning in Grade 9 Science and its relationship in academic performance of learners. The study was implemented in a large public secondary school. Level of preparedness of parents was determined through a researcher-developed survey questionnaire while the academic performance was the learners’ first quarter grade in Science 9. After the answering of survey, results were subjected to appropriate statistical analysis. The numerical data gathered from the instruments were subjected to specific descriptive and inferential statistical treatment. Significant differences were found on the parents’ level of preparedness as well as students’ academic performance when grouped according to socio-economic status and educational attainment. Parents and guardians’ preparedness affects academic performance in Grade 9 Science. They are most likely to be supportive on the education of their learners in terms of physical and emotional domains of readiness as they have obtained high results on the survey given to them.